If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 21 = 7(3b + -9) Reorder the terms: 21 = 7(-9 + 3b) 21 = (-9 * 7 + 3b * 7) 21 = (-63 + 21b) Solving 21 = -63 + 21b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-21b' to each side of the equation. 21 + -21b = -63 + 21b + -21b Combine like terms: 21b + -21b = 0 21 + -21b = -63 + 0 21 + -21b = -63 Add '-21' to each side of the equation. 21 + -21 + -21b = -63 + -21 Combine like terms: 21 + -21 = 0 0 + -21b = -63 + -21 -21b = -63 + -21 Combine like terms: -63 + -21 = -84 -21b = -84 Divide each side by '-21'. b = 4 Simplifying b = 4
| 2T^2-2T-4=t^2-5t+6 | | -10x+4y=14 | | (8-y)(5y-9)=0 | | 8(9f-5)=28 | | -5x+3y=11 | | 2ag+5bg=3bc | | 3x+6=10x-10 | | 7(9a+8w)9(6a-4w)= | | b-7+7b=20 | | 5(y+3)=-4y-24 | | 3(y-7)=42 | | 20.87=4g+3.59 | | 12x(y)=12(xy) | | -4(-2)(-4)= | | -8t=96 | | b-4+8b=16 | | f(x)=2x^3+22x^2+60x | | -14=3-C+(95c) | | 4(8+7x)=-35 | | .04(70)+.25x=.15(x+70) | | -5(r+9)=-72 | | 4(x-9)+17=3x-11 | | 3x-8c+7=-18 | | 3x+3-x+2=2x+5 | | -3x(4+9)=8x(3-2) | | 800=400+40x | | 7(t*t+5t-9)+t=t(7t-2)13 | | 7(x-2)=2x+16 | | 3(-x-5)+14=x-9 | | 24-4x=10 | | 0.5x-2.4=0.6 | | -h+5=-2 |